2002
DOI: 10.3406/intel.2002.1072
|View full text |Cite
|
Sign up to set email alerts
|

Sensory performances in the human foetus : a brief summary of research

Abstract: A growing body of evidence is available about the functioning of foetal sensory systems during gestation. This article aims at reviewing data concerning (i) the accession of sensory stimulation to the foetal sensory receptors, (ii) the sequence of functional development of the major sensory systems (iii) the physiological and behavioural responses of foetuses to various types of stimulation. Human data are confronted to data collected in other mammalian species. Most studies have investigated auditory and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 125 publications
0
15
0
1
Order By: Relevance
“…Future studies should be targeted toward (a) reconciling strikingly different neural response patterns and the largely similar self‐reported affective judgments of textured stimuli; (b) characterizing neural responses to more directly social versus nonsocial tactile stimulation; as well as addressing (c) individual differences; and (d) the neural signatures of touch in younger samples. The early development of the somatosensory system [Lecanuet & Schaal, ] and predictive value of tactile responsiveness in infants for later development of ASD [Baranek, ] make neural differences in somatosensory responses a promising candidate for an early biomarker for a subgroup of individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should be targeted toward (a) reconciling strikingly different neural response patterns and the largely similar self‐reported affective judgments of textured stimuli; (b) characterizing neural responses to more directly social versus nonsocial tactile stimulation; as well as addressing (c) individual differences; and (d) the neural signatures of touch in younger samples. The early development of the somatosensory system [Lecanuet & Schaal, ] and predictive value of tactile responsiveness in infants for later development of ASD [Baranek, ] make neural differences in somatosensory responses a promising candidate for an early biomarker for a subgroup of individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…But even if one were to assume no innate linguistic knowledge in humans, the language-learning newborn still would not be a blank slate. The fetal auditory system begins functioning during the third trimester of pregnancy, allowing some environmental sounds (including a low-pass filtered version of the mother's voice) to pass through the mother's body to the womb (e.g., Lecanuet & Schaal 2002). This allows the human fetus to get a jumpstart on learning her native language by eavesdropping on her mother in the months preceding birth (Saffran et al 2006).…”
Section: The Beginning Statementioning
confidence: 99%
“…But, in recent decades, a growing body of evidence, based on numerous studies on the perceptual and cognitive abilities of fetuses and newborns, has demonstrated that sensory systems are relatively mature at (term) birth, at both peripheral and central levels (for reviews: e.g. [2], [3], [4], [5], [6]). There are different possible explanations for this early undervaluation: one main aspect is that neonates are non-verbal individuals, which means that the initial assessment of their sensory abilities was made by adults caretakers that did not necessarily share the same sensory world; moreover, the immaturity of neonates may have been overestimated, by supposing a priori limited sensory and cognitive skills; and at the same time, there were technological limitations that prevented the direct observation of fetal behavior and the study of infant brain function.…”
Section: Introductionmentioning
confidence: 99%